2019
DOI: 10.3390/antiox8080300
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Pharmacology of the Kazakh Crataegus Almaatensis Pojark: An Asian Herbal Medicine

Abstract: Crataegus almaatensis, an endemic ornamental plant in Kazakhstan is used in popular medicine due to its cardiotonic properties. The most studied species of the same genus are commonly found in Europe, which shows the importance of having the Kazakh species validated via its chemical and pharmacological studies. High-speed countercurrent chromatography (HSCCC) operated under optimized conditions enabled an isolation of the three main compounds from the aqueous phase of the leaves ethanol extract, further identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Taking as an example a species like C. crusgalli L. that may often grow to tree size, and thus flower and fruit abundantly, hawthorns can be important in wildlife management, providing as they do shelter and food for mammals, birds, and invertebrates, notably insect pollinators and other flower visitors, and frugivorous birds and small mammals [8,9]. Finally, hawthorns have been used in traditional medicine virtually wherever they occur, and are studied for their potential role in allopathic medicine, notably in relation to cardiovascular disease [3,4,[10][11][12][13][14][15][16]. For these reasons there is merit in seeking a better understanding of the evolutionary and ecological phenomena related to hawthorns, as the plants may be valuable in themselves as sources of foods and medicines, and for their ecological roles in both the man-made and natural habitats where they occur.…”
Section: Introductionmentioning
confidence: 99%
“…Taking as an example a species like C. crusgalli L. that may often grow to tree size, and thus flower and fruit abundantly, hawthorns can be important in wildlife management, providing as they do shelter and food for mammals, birds, and invertebrates, notably insect pollinators and other flower visitors, and frugivorous birds and small mammals [8,9]. Finally, hawthorns have been used in traditional medicine virtually wherever they occur, and are studied for their potential role in allopathic medicine, notably in relation to cardiovascular disease [3,4,[10][11][12][13][14][15][16]. For these reasons there is merit in seeking a better understanding of the evolutionary and ecological phenomena related to hawthorns, as the plants may be valuable in themselves as sources of foods and medicines, and for their ecological roles in both the man-made and natural habitats where they occur.…”
Section: Introductionmentioning
confidence: 99%
“…In our work, hyperoside showed the lowest in vitro antioxidant action among the tested compounds; however, this biomolecule has shown antioxidant properties in in vivo [55,56,57] and cell-based models [56,58,59]. The antioxidant activity of hyperoside is also highlighted by its anti-inflammatory effects as shown by several reports [54,60,61,62]. Other promising pharmacological properties include the treatment of cancer [63,64], obesity [65], arthritis [61], and diabetes [66].…”
Section: Discussionmentioning
confidence: 48%
“…Similar results were recently reported by Ren et al [50], which showed that hyperoside had a minimal bacteridal concentration (MIC) of 250 μg/mL against S. aureus ATCC 25923. Although hyperoside has been found as a component of some plants with antimicrobial and antioxidant activity [50,51,52,53,54], its mechanism of antimicrobial action of has not been reported yet. In our work, hyperoside showed the lowest in vitro antioxidant action among the tested compounds; however, this biomolecule has shown antioxidant properties in in vivo [55,56,57] and cell-based models [56,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…A total of eight compounds were separated from the 70% methanol extract of M. volcanica and identified via NMR, EI-MS, and LC-MS analysis as well as by comparison with a previously published paper and a standard compound (rutin). These compounds are shikimic acid ( 2 ) [ 29 ], gallic acid ( 3 ) [ 30 ], protocatechuic acid ( 4 ) [ 31 ], 4,4′-dihydroxy-3,3′-imino-di-benzoic acid ( 6 ) [ 32 ], miquelianin ( 7 ) [ 33 ], rutin ( 8 ) [ 34 ], quercitrin ( 9 ) [ 35 ], and quercetin ( 10 ) [ 36 ], as shown in Table S2 and Figure 6 . Moreover, the raw NMR spectra are shown in Figures S2–S9 .…”
Section: Resultsmentioning
confidence: 99%